PENGARUH TOKOH PUNAKAWAN SANGUT DAN DELEM TERHADAP PEMAHAMAN PEMBACA KARTUN EDITORIAL SANGUT DELEM DI HARIAN BALI POST - Witari, Ni Nyoman Sri (Universitas Pendidikan Ganesha, 2012)
Sangut and Delem who are two servant figures in the Balinese shadow puppets grip are adopted asan editorial cartoon of Bali Post newspaper. The concept of plot and character to the traditional characterizationsturns into a special appeal when they are interpreted as editorial cartoons. So that the election of theircharacters as the main characters is very interesting to study the importance of considering the editorial role inbuilding the image of a newspaper. Furthermore the election of their characters as the main characters is veryinteresting to study given the mission to preserve traditional cultural symbols to reinforce the character of theyoung generation which is an important agenda.This study used a questionnaire instrument to collect data and are presented in the form of descriptiveanalysis through simple charts and tables. From the results of the analysis it is showed that puppet characters Sangut and Delem remains relevant and are used as an editorial cartoon today.Keywords: character, cartoon editorial, punakawan Sangut Delem